2012
DOI: 10.1371/journal.pone.0035201
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Investment: Individual Reproduction of Ant Queens Increases with Age

Abstract: The pattern of age-specific fecundity is a key component of the life history of organisms and shapes their ecology and evolution. In numerous animals, including humans, reproductive performance decreases with age. Here, we demonstrate that some social insect queens exhibit the opposite pattern. Egg laying rates of Cardiocondyla obscurior ant queens increased with age until death, even when the number of workers caring for them was kept constant. Cardiocondyla, and probably also other ants, therefore resemble t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 37 publications
5
62
3
Order By: Relevance
“…The reproduction/life-span trade-off is absent in comparisons among castes, since queens are able to enjoy both longer life spans and higher reproductive output compared to workers (Keller and Genoud, 1997), much like germline cells compared to somatic cells (Boomsma et al, 2014). Furthermore, even among queens the usual trade-offs do not seem to apply, as recent studies have shown that high reproductive success does not compromise life-spans of the queens (Heinze and Schrempf, 2012;Heinze et al, 2013). Social insect queens might not suffer from reproductive trade-offs similarly to solitary organisms, since the costs of reproduction are mostly carried by the workers who take care of the brood and maintain colony homeostasis.…”
Section: Life History Trade-offsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reproduction/life-span trade-off is absent in comparisons among castes, since queens are able to enjoy both longer life spans and higher reproductive output compared to workers (Keller and Genoud, 1997), much like germline cells compared to somatic cells (Boomsma et al, 2014). Furthermore, even among queens the usual trade-offs do not seem to apply, as recent studies have shown that high reproductive success does not compromise life-spans of the queens (Heinze and Schrempf, 2012;Heinze et al, 2013). Social insect queens might not suffer from reproductive trade-offs similarly to solitary organisms, since the costs of reproduction are mostly carried by the workers who take care of the brood and maintain colony homeostasis.…”
Section: Life History Trade-offsmentioning
confidence: 99%
“…While comparative data from natural populations is rare and extremely labor-intensive to achieve, and unavailable apart from a few model systems (Cole, 2009;Gordon, 2010), there is potential in experimentally accessible colonies with shorter life spans (Heinze and Schrempf, 2012;Heinze et al, 2013). Even if social insect life histories have been described in an organismal light for almost 40 years, there is much unexplored potential to experimentally study how life-history trade-offs that regulate e.g., colony aging evolve at the superorganismal level.…”
Section: Life History Trade-offsmentioning
confidence: 99%
“…Overall, empirical evidence for the age-related reproductive patterns that are predicted by the cost of reproduction hypothesis is mixed (Table 1), but support for age-dependent terminal investment has been found in both sexes in various mammals, reptiles, and insects (Table 1; supplementary table S1). For example, queens of the ant Cardiocondyla obscurior have been shown to increase their rate of egg production with age, even months after mating (Heinze and Schrempf 2012). …”
Section: The Terminal Investment Hypothesis In Reviewmentioning
confidence: 99%
“…Previous studies have shown that germline-ablated worms had an extended lifespan [6], and sterile females also showed greater longevity compared with fertile flies [7]. Although most animal species show a gradual decline in reproduction with age [8], social insect queens are thought to be the only animals known that can live for long periods while also producing many offspring per day [9]. Because of their abnormal characteristics implying the presence of an extraordinary anti-aging mechanism, social insect queens have attracted much attention, and they are promising subjects for aging research [10].…”
Section: Introductionmentioning
confidence: 99%